Razlike v šolskih dosežkih deklic in dečkov ter protislovja regulacije spolov - Tašner, Veronika (Šolsko polje, 2011)
At first glance, statistical data in education appear to paint a more favorable picture for females in comparison to males (an increase in the average education level of women at a faster pace, and girls' performance on final secondary school examinations as well as on the PISA and TIMSS tests). For the past two decades, these data have been used as an argument in favor of the hypothesis that the Slovenian education system favors girls over boys. This article points out the danger of reviving the hypotheses about male and female natures, which are the root of assessments about girls being ascribed a privileged role, and diff erences in school achievement within the categories of males and females, which are the consequence of growing social (and political) inequality. Th e analysis of diff erences in girlsć and boysć achievement proceeded from the conceptualization of gender identity as a relation ratio supported by the governing constructs of masculinity and femininity. Within the circumstances of increasing uncertainty and competitiveness, these constructs are not inclined toward treating males and females equally.
Keywords: achievement gain; šolska uspešnost; spolna razlika; sex difference; girl; deklica; vzgoja in izobraževanje; šolski dosežki; izobrazba; feminism; feminizem; spol; razlike med spoloma; raziskave